K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 8 2016

a) 2 - 4a + 4bc + 2a2 - 2b2 - 2c2

    => 2.( 1 - 2a + 2bc + a2 - b2 - c2)

b) 3x2 + 9cd.(2 - 3cd) - 30xy - 3 + 75y2

    => 3x2 + 18cd - 27c2d2 - 30xy - 3 + 75y

    => 3.( x2 + 6cd - 9c2d2 - 10xy -1 + 25y2)

(b+a)(c+2a)(c+2b)

20 tháng 8 2017

\(a^2+b^2+2a-2b-2ab=a^2-2ab+b^2+2\left(a-b\right)\)

                                                     \(=\left(a-b\right)^2+2\left(a-b\right)\)

                                                      \(=\left(a-b\right)\left(a-b+2\right)\)

20 tháng 8 2017

\(4a^2-4b^2-4a+1=4a^2-4a+1-\left(2b\right)^2\)

                                          \(=\left(2a-1\right)^2-\left(2b\right)^2\)

                                            \(=\left(2a-1-2b\right)\left(2a-1+2b\right)\)

3 tháng 10 2015

1)

b) \(\left(x-z\right)^2-y^2+2y-1\)

\(=\left(x^2-2xz+z^2\right)-\left(y-1\right)^2\)

\(=\left(y-z\right)^2-\left(y-1\right)^2\)

\(=\left[\left(x-z\right)+\left(y-1\right)\right]\cdot\left[\left(x-z\right)-\left(y+1\right)\right]\)

\(=\left(x-z+y-1\right)\cdot\left(x-z-y-1\right)\)

 

5 tháng 11 2017

a)=(a2+2ab+b2) +(b2-c2) +(ab+ac)-c2

=(a+b)2 -c2 +(b+c)(b-c) +a(b+c)

=(a+b-c)(a+b+c)+(b+c)(a+b-c)

=(a+b-c)(a+2b+2c)

c)a4+2a3+1

=a4 +a3+a3+a2-a2-a+a+1

=a3(a+1)+a2(a+1)-a(a+1)+(a+1)

=(a+1)(a3+a2-a+1)

d)x5+x+1

=(x5+x4+x3)-x4-x3-x2+x2+x+1

=x3(x2+x+1) -x2(x2+x+1) +(x2+x+1)

=(x2+x+1)((x3-x2+1)

e)x8+x4+1

=(x4)2 +2x4+1-x4

=(x4+1)2 -x4

=(x4+1+x2)(x4+1-x2)

=(x4+2x2+1-x2)(x4-x2+1)

=[(x2+1)2-x2 ](x4-x2+1)

=(x2+1-x)(x2+1 )(x4-x2+1)

2 tháng 11 2018

\(x^8+x^4+1\)

\(=x^8+2x^4+1-x^4\)

\(=\left(x^4+1\right)^2-x^4\)

\(=\left(x^4+x^2+1\right)\left(x^4-x^2+1\right)\)

\(=\left(x^2-x+1\right)\left(x^2+x+1\right)\left(x^4-x^2+1\right)\)

24 tháng 8 2016

2a2b2+2a2c2+2b2c2-a4-b4-c4

=4a2b2-(a4+2a2b2+b4)+(2b2c2+2a2c2)-c4

=2(ab)2-(a+b)2+2c2(a2+b2)+c4

=2(ab)2-[(a+b)2-2c2(a2+b2)+c4]

=2(ab)2-(b2+a2-c2)2

=[(a+b)2-c2][-(a-b)2+c2]

=(a+b-c)(a+b+c)(c-a+b)(a+c-b)

 

25 tháng 8 2016

\(2a^2b^2+2a^2c^2+2b^2c^2-a^4-b^4-c^4\)

\(=4a^2b^2-\left(a^4+2a^2b^2+b^4\right)+\left(2b^2c^2+2a^2c^2\right)-c^4\)

\(=2\left(ab\right)^2-\left(a+b\right)^2+2c^2\left(a^2+b^2\right)+c^4\)

\(=2\left(ab\right)^2-\left[\left(a+b\right)^2-2c^2\left(a^2+b^2\right)+c^4\right]\\ =2\left(ab\right)^2-\left(b^2+a^2-c^2\right)^2\)

=\(\left[\left(a+b\right)^2-c^2\right]\left[-\left(a-b\right)^2+c^2\right]\\ =\left(a+b+c\right)\left(a+b+c\right)\left(c-a+b\right)\left(a+c-b\right)\)

10 tháng 8 2016

a)\(\left(a^3-b^3\right)+\left(a-b\right)^2\)

\(=\left(a-b\right)\left(a^2+ab+b^2\right)+\left(a-b\right)^2\)

\(\left(a-b\right)\left(a^2+ab+b^2+a-b\right)\)

b) \(\left(8a^3-27b^3\right)-2a\left(4a^2-9b^2\right)\)

\(=\left(2a-3b\right)\left(4a^2+6ab+9b^2\right)-2a\left(2a-3b\right)\left(2a+3b\right)\)

\(=\left(2a-3b\right)\left(4a^2+6ab+9b^2-4a^2-6ab\right)\)

\(=\left(2a-3b\right)\cdot9b^2\)

 

 

10 tháng 8 2016

\(=\left(a-b\right)\left(a^2+ab+b^2\right)+a^2-2ab+b^2\)

= ...........